Psychometric validation of questionnaire towards awareness of ototoxicity risk due to solvent exposure - Ainul Naqueah, Zainal Abidin; Mohd Shukri, Aris; Ailin, Razali; Norazura, Ismail (Universiti Putra Malaysia Press, 2022)
Noise is a major risk factor for hearing problem; however, chemicals also contribute to the current prevalence of hearing problem worldwide. In many countries, industrial practices are performed without considering the possible ototoxic health consequences of solvents. Therefore, measuring the awareness level of ototoxicity risk has become a major concern. This study aims to validate a questionnaire to measure the awareness of ototoxicity risk among paint and coating manufacturing industriess. Methods: The questionnaire was adapted from Alnuman and Ghnimat (2019). The translation process in this study employed forward-only translations. The questionnaire was assessed in terms of its content and face validity before it was administered to 80 paint and coating manufacturing workers to determine the internal consistency reliability. Results: Content validation of this questionnaire showed an excellent content validity score with Content Validity Ratio (CVR) for each item and the mean score for all items included in the instruments; Content Validity Index (CVI) were both 1.0. Face validation resulted in an overall scale-level FVI of above 0.80, with an average index (S-FVI/Ave) for clarity and comprehension at 1.0 and 0.99, respectively. Meanwhile, the universal agreement index (S-FVI/UA) for clarity and comprehension of the questionnaire scale were both 0.90. Cronbach’s alpha for internal consistency was excellent (0.82). Conclusion: The questionnaire to assess awareness level of ototoxicity risk from solvent exposure is valid and reliable. It demonstrates good psychometric properties. However, future research should look at additional types of validity and reliability, such as construct validity and test-retest reliability.